PEMBIAYAAN BANTUAN OPERASIONAL SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PADA SMP NEGERI 1 SYAMTALIRA BAYU KABUPATEN ACEH UTARA - Herman .; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Financing education most important input components in the implementation of educational programs in schools and the need for guidance as a foundation of the foundation so that the financial management of schools can be done well. The objective of this research was to determine the understanding of the school of government policies related to financing school operational assistance, financing management of school operational assistance and its relevance to education quality improvement initiatives, and school problems in the process of financing school operational assistance in improving the quality of education at SMPN 1 Syamtalira Bayu North Aceh District. This study uses a qualitative approach to data collection through interviews, observation and documentation. The data analysis was done through data reduction, data display, and verification. Subjects were principals, vice principals, and teachers. Keywords: Financing Education, SOA, and Quality of Education.